Electroflocculation of river water using iron and aluminium electrodes - Mashamaite, Aubrey Nare (My University, 2008)
A novel technology in the treatment of river water, which involves an electrochemical treatment technique to produce domestic or drinking water is being investigated using aluminium and iron electrodes in an electrochemical circuit. Coagulation and flocculation are traditional methods for the treatment of polluted water. Electrocoagulation presents a robust novel and innovative alternative in which a sacrificial metal anode treats water electrochemically. This has the major advantage of providing mainly active cations required for coagulation and flocculation, without increasing the salinity of the water. Electrocoagulation is a complex process with a multitude of mechanisms operating synergistically to remove pollutants from the water. A wide variety of opinions exist in the literature for key mechanisms. A lack of a systematic approach has resulted in a myriad of designs for electrocoagulation reactors without due consideration of the complexity of the system. A systematic, holistic approach is required to understand electrocoagulation and its controlling parameters. An electrocoagulation-flotation process has been developed for water treatment. This involved an electrolytic reactor with aluminium and/or iron electrodes. The water to be treated (river water) was subjected to coagulation, by Al(III) and Fe(II) ions dissolved from the electrodes, resulting in floes floating after being captured by hydrogen gas bubbles generated at the cathode surfaces. Apparent current efficiencies for AI and Fe dissolution as aqueous Al(III) and Fe(II) species at pH 6.5 and 7.8 were greater than unity. This was due to additional chemical reactions occurring parallel with electrochemical AI and Fe dissolution: oxygen reduction at anodes and cathodes, and hydrogen evolution at cathodes, resulting in net (i.e. oxidation plus reduction) currents at both anodes and cathodes. Investigation results illustrate the feasibility of ferrous and aluminium ion electrochemical treatment as being a successful method of water treatment. Better results were achieved under conditions of relatively high raw water alkalinity, relatively low raw water turbidity, and when high mixing energy conditions were available.
M. Tech. (Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Water purification; Electrocoagulation; Vaal Dam; Flotation; Electrochemical treatment; Electroflocculation; River water treatment; 628.162; Drinking water -- Purification -- South Africa; Water quality